2017
DOI: 10.18060/21409
|View full text |Cite
|
Sign up to set email alerts
|

Giving Behavior in Turkey: Determinants of Individual Donations and Volunteering

Abstract: <p>This paper shares the results of a recent study about the giving of donations or time (volunteering) among citizens of Turkey.  It examines the determinants of giving in light of recent research on this topic from other countries.  We find level of education and institutional trust to be positively associated with giving, particularly to civil society organizations.  In contrast to other studies, age is not associated with giving and men give at a higher rate than women.  We compare these results with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Previous literature argues that people with a higher education are more likely to have more financial resources, stronger prosocial attitudes, higher cognitive abilities and are more trusting, which increases their likelihood and level of charitable giving (Bekkers and Wiepking, 2011b;Wiepking and Maas, 2009). Empirical studies confirm these relationships not only for the U.S. and Western Europe, but also for non-Western countries such as Iran and Turkey (Aghababa et al, 2015;Çarkoğlu et al, 2017). In China, Party members typically have higher levels of education (Bian et al, 2001;Hauser, 2003).…”
Section: Human Resourcesmentioning
confidence: 92%
“…Previous literature argues that people with a higher education are more likely to have more financial resources, stronger prosocial attitudes, higher cognitive abilities and are more trusting, which increases their likelihood and level of charitable giving (Bekkers and Wiepking, 2011b;Wiepking and Maas, 2009). Empirical studies confirm these relationships not only for the U.S. and Western Europe, but also for non-Western countries such as Iran and Turkey (Aghababa et al, 2015;Çarkoğlu et al, 2017). In China, Party members typically have higher levels of education (Bian et al, 2001;Hauser, 2003).…”
Section: Human Resourcesmentioning
confidence: 92%
“…Accordingly, researchers have been called to identify diverse ways to motivate individuals in their twenties, thirties, and early forties and to contribute to the well‐being of society (Miori, 2023; Sheng & Basha, 2022). Furthermore, research on motivations to engage in charitable activities in Türkiye revealed that there are various motives that affect charitable behaviors (e.g., Campbell & Çarkoğlu, 2019; Çarkoğlu et al, 2017). Turkish people were found to donate their time and/or money with both altruistic (e.g., helping the needy, serving society, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Brazil is a middle-income country with significant income inequality and poverty (Alvaredo, 2018), making it a unique setting to test the existing findings on philanthropy and its predictors, which have mainly come from developed Western countries (Baillie Smith et al, 2018;Çarko glu et al, 2017;Heist et al, 2022;Neumayr & Pennerstorfer, 2021;Yang & Konrath, 2023) Brazil is primarily a Catholic country, but it has witnessed a growing population of Evangelicals and individuals identifying as non-religious (IBGE, 2010). Additionally, Brazil is experiencing an aging demographic, with over 56% of its population aged 30 or older and 51% of women (IBGE, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This complexity may be attributed, in part, to the challenges inherent in comparing findings from studies using diverse methodologies and sample compositions (Neumayr & Pennerstorfer, 2021). Furthermore, research on charitable giving in low‐ and middle‐income countries remains sparse (Baillie Smith et al, 2018; Çarkoğlu et al, 2017; Neumayr & Pennerstorfer, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation